2002
DOI: 10.21236/ada402347
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of the Johnson-Holmquist II (JH-2) Constitutive Model into DYNA3D

Abstract: This report describes the implementation of a fully three-dimensional rate, pressure, and damage-dependent constitutive model for brittle materials such as ceramics into the explicit, Lagrangian finite element code DYNA3D. The model, otherwise known as the Johnson-Holmquist II QH-2) ceramic model, has also been implemented into CTH, EPIC, and LS-DYNA, and is used extensively in modelling the brittle response of ceramics in armor applications. The DYNA3D material driver was used to verify the model implementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 5 publications
1
6
0
Order By: Relevance
“…Their investigation included simulation of discrete micro-structure, layer modeling and consideration of continuous change of material properties. Recently, Thamburaj et al (2003) have implemented the damage model by Johnson and Holmquist (1994) into the dynamic finite element code DYNA3D (Gazonas, 2002), and investigated the effect of graded strength on damage propagation in continuously non-homogeneous materials. They observed that introducing different strength gradation can change the location of site of maximum damage, which may have important implication in the design of impact resistant materials and structures.…”
Section: Introductionmentioning
confidence: 99%
“…Their investigation included simulation of discrete micro-structure, layer modeling and consideration of continuous change of material properties. Recently, Thamburaj et al (2003) have implemented the damage model by Johnson and Holmquist (1994) into the dynamic finite element code DYNA3D (Gazonas, 2002), and investigated the effect of graded strength on damage propagation in continuously non-homogeneous materials. They observed that introducing different strength gradation can change the location of site of maximum damage, which may have important implication in the design of impact resistant materials and structures.…”
Section: Introductionmentioning
confidence: 99%
“…Common to all mechanical analyses of engineering materials and their behavior in structural components is the need for constitutive models that link the states of stress and strain (Runesson, ). There are specific constitutive material models used in FEM‐based explicit dynamics analyses for brittle material modelling such as Johnson–Holmquist (JH‐I, JH‐II, and JH‐III), Drucker‐Prager Strength, and RHT Concrete damage models (ANSYS Documentation, ; Gazonas, ). Not only physical tensile/compression tests but also other mechanical experimental tests, curve‐fitting calculations and strain rate consideration are essential to define the parameters used in most of these material models (Cronin, McIntosch, Kaufmann, Bui, & Berstad, ; Murakami & Kamiya, ; Ruggiero, Iannitti, Bonora, & Ferraro, ).…”
Section: Methodsmentioning
confidence: 99%
“…A parameter  is used to describe the fraction of elastic energy that is converted to potential hydrostatic energy. The numerical implementation of the JH2 model for the LS-DYNA software used in this work is described in [29].…”
Section: Brittle Materials Modelmentioning
confidence: 99%